The unique chemical and microbiological signatures of an array of bottled drinking water - Nadreen, Yasmeen M.; Vrouwenvelder, Johannes S.; Saikaly, Pascal E.; Gonzalez-Gil, Graciela (Frontiers in Microbiology, 2024)
The bottled drinking water market has seen significant growth and diversification, yet the selection criteria lack scientific basis, as all must adhere to stringent health standards. Prior studies predominantly focused on chemical quality, with limited assessments of microbial quality using methods prone to underestimation. Moreover, insufficient research explores the impact of packaging materials and temperatures optimal for mesophilic growth on microbial quality. To understand the unique characteristics and justify the distinction among different types of bottled waters, a comprehensive analysis encompassing both chemical and microbiological aspects is imperative. Addressing these gaps, our study examines 19 diverse bottled water brands comprising purified, mineral, artesian, and sparkling water types from Saudi Arabia and abroad. Our findings reveal distinct chemical compositions among bottled waters, with notable variations across types. Flow cytometry analysis reveals significant differences in bacterial content among water types, with natural mineral waters having the highest concentrations and treated purified waters the lowest. Bacterial content in plastic-bottled mineral water suggests it may be higher than in glass-bottled water. Flow cytometry fingerprints highlight separate microbial communities for purified and mineral waters. Additionally, temperatures favorable for mesophilic growth reveal varying microbial responses among different types of bottled waters. Some variation is also observed in mineral water bottled in plastic versus glass, suggesting potential differences that warrant further investigation. 16S rRNA gene sequencing identifies unique microbial taxa among different mineral waters. Overall, our study underscores that all bottled waters meet health regulations. Furthermore, the combined chemical and microbial profiles may serve as authenticity indicators for distinct bottled water types. This study can serve as a basis for future research on the environmental impact of bottled water transportation, suggesting that locally produced water may offer a more sustainable option.